Inhibition of T lymphocyte mitogenesis by 1,25-dihydroxyvitamin D3 (calcitriol). - Rigby, W F (1984)
Recent studies have suggested that vitamin D may have other important biologic activities in addition to its well-characterized role in the maintenance of calcium homeostasis. Discovery of cytosolic receptors for vitamin D in human peripheral blood monocytes and lectin-stimulated lymphocytes prompted us to study the effects of 1,25-dihydroxyvitamin D3 (calcitriol), the most biologically active metabolite of vitamin D, upon phytohemagglutinin (PHA)-induced lymphocyte blast transformation. We have found that calcitriol is a potent inhibitor of PHA-induced lymphocyte proliferation, achieving 70% inhibition of tritiated thymidine incorporation after 72 h in culture. Furthermore, calcitriol suppressed interleukin-2 (IL-2) production by PHA-stimulated peripheral blood mononuclear cells in a concentration-dependent fashion. Lastly, the suppressive effect of calcitriol on cellular proliferation was partially reversed by the addition of saturating amounts of purified IL-2. We conclude that calcitriol is a potent inhibitor of PHA-induced lymphocyte blast transformation and that this effect is mediated, in part, through suppression of IL-2 production. Thus, calcitriol appears to possess immunoregulatory properties that have been unappreciated heretofore.